MODULE PLANS AS A MEANS FOR EFFICIENT IMPLEMENTATION OF UNIVERSITY EDUCATIONAL PROGRAMS ON THE BASIS OF FSES3+ - Mikhail V. Gryazev; Sergei A. Rudnev; Marina A. Anisimova; Igor S. Blyakherov (Высшее образование в России)
The article deals with the problems arising in connection with the development of curricula for basic educational programs based on the Federal State Educational Standard 3+ in multi-disciplinary higher educational institutions. The article also proposes some improvements to the educational system basing on the experience of Tula State University in implementing module-based curriculum as a step for transition to asynchronous education.